2021
DOI: 10.3390/s21092906
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographic Assessment of the Efficacy of Deep Dry Needling versus the Ischemic Compression Technique in Gastrocnemius of Medium-Distance Triathletes

Abstract: Several studies have shown that gastrocnemius is frequently injured in triathletes. The causes of these injuries are similar to those that cause the appearance of the myofascial pain syndrome (MPS). The ischemic compression technique (ICT) and deep dry needling (DDN) are considered two of the main MPS treatment methods in latent myofascial trigger points (MTrPs). In this study superficial electromyographic (EMG) activity in lateral and medial gastrocnemius of triathletes with latent MTrPs was measured before a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 68 publications
0
7
0
1
Order By: Relevance
“…According to the type of participants, athletes and healthy non-athletic subjects were involved in the analyzed studies. It should be remarked that studies involving athletes [ 37 , 38 , 39 , 40 , 41 , 43 ] showed no positive results on any of the outcomes analyzed, except for the study conducted by Devereux et al [ 41 ], which obtained significant results on jump height. Therefore, due to the heterogeneity of the sport modalities included, we cannot provide a categorized overview according to the influence of the characteristics of each sport modality on the outcomes.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…According to the type of participants, athletes and healthy non-athletic subjects were involved in the analyzed studies. It should be remarked that studies involving athletes [ 37 , 38 , 39 , 40 , 41 , 43 ] showed no positive results on any of the outcomes analyzed, except for the study conducted by Devereux et al [ 41 ], which obtained significant results on jump height. Therefore, due to the heterogeneity of the sport modalities included, we cannot provide a categorized overview according to the influence of the characteristics of each sport modality on the outcomes.…”
Section: Discussionmentioning
confidence: 94%
“…A total of 426 subjects were involved in the studies included in the systematic review, assuming that the studies carried out by De-Pedro et al [ 37 , 38 , 39 ] involved the same participants. Albin et al [ 34 ] is the study with the highest sample size, with 102 participants.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations